SELF-MANAGEMENT DIET AND RANDOM PLASMA GLUCOSE CONTROL OF PATIENT WITH TYPE 2 DIABETES MELLITUS AT PUSKESMAS ALUN-ALUN GRESIK - Vincentius Michael Willianto; Robertus Saldi Cundawan; Dana Parama Julius; I Dewa Gede Pangestu Banu Ananta; Sancha Melarisa Hilarius; Christin Setiawan; Alecia Fransiska Khorianto; Valerie Grecia; Paul Jhosua Dayoh; Jasinda Dwiranti; Ivita Tahta Murbarani; Elicia Vincensa; Ahmad Taufik; Lukas Slamet Rihadi; Inge Wattimena; Florentina Sustini; Steven Wijono; Dewa Ayu Liona Dewi; Yudhiakuari Sincihu (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: Diabetes Mellitus (DM) is a non-communicable metabolic disease characterized by the pancreas not being able to produce insulin and a decrease in insulin receptor sensitivity. Epidemiological data show the prevalence of type 2 diabetes mellitus is high in Indonesia and estimated to increase by more than 2.5 times in 2030 compared to 2020. Several factors play an important role in the development and management of diabetes cases, including the management of a good independent diet. People with DM who do not pay attention to their diet can trigger complications and disability. Objective: This study aims to determine the correlation between independent diet management and blood sugar control in patients with type 2 diabetes mellitus. Methods: This study used an observational analytic method with a cross sectional design. The sampling technique was consecutive sampling. Self-management assessment of diet used the Self-Management Diabetic Diet Questionnaire (SMBDQ) which has been adjusted and tested for validity and reliability. Blood sugar measured using a glucometer. Data processing was conducted using Kendall's tau C with a significance level of 95% (α=0.05). Results: There was 79 respondents. There was a correlation with a significance value (P= 0.002) with a low correlation (τ=0.255) between independent diet management and current blood sugar control in patients with type 2 diabetes mellitus. Conclusion: Independent diet management has a significant correlation with blood sugar control in patients type 2 diabetes mellitus. Keywords: Diabetes mellitus, independent diet management, Random Plasma Glucose, Self-Management Diabetic Diet Questionnaire.